Sustainable Development Innovation: “Increasing SME Competence in Resources Aspects” - Rodhiah Rodhiah; Nur Hidayah; Toto Mujio Mukmin (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
One of the main problems in the development of the Creative Industry in Indonesia is the lack of competent Human Resources (HR) in the process of utilizing existing resources. This is because there is no innovation model for sustainable organizational competency development where the influence and impact can be measured and used as a guide in the future. The main purpose of this research is to produce a Sustainable Development Innovation model, especially in the field of Organizational Competence in Small and Medium Enterprises (SMEs) in Serang, South Tangerang, Tangerang City, and Cilegon areas. This model contains a matrix of continuous innovation that will make organizational competencies can be fulfilled properly. The sample of this research is SMEs in the potential craft sector. Research data were collected through in-depth interviews, documentation studies, and using secondary data from the local Koperindag Office (Cooperative, Industrial, Trade, Market and Mining Office). Based on the data that has been collected, then the data analyzed and made a matrix model of Sustainable Development Innovation based on various existing sustainable development theories and one of the results is an organizational competency analysis framework for SMEs. The model from this research is expected to be an efficient framework that is useful for analyzing the direct and indirect consequences of various inputs in the SME world, both in Serang, South Tangerang, Tangerang City, and Cilegon as well as throughout Indonesia.